Saving in Asia and Issues for Rebalancing Growth - Shikha Jha; Eswar Prasad; Akiko Terada-Hagiwara (Asian Development Bank (ADB), 2009)
This paper assesses the role of consumption and saving in Asia's growth. It examines the composition of national saving, analyzes what forces drive saving rates, and draws policy conclusions from the analysis that are relevant for the economies in the region and which might play an important part in rebalancing global growth. The paper identifies a number of issues. A rapid rise in the profitability of state-owned and private enterprises together with distorted dividend policies and underdeveloped financial markets in the People's Republic of China (PRC) seem to have contributed to the corporate sector saving spiral. Rising corporate saving rates in India can be attributed to lower corporate tax rates, customs duty, and interest rates along with restructuring of firms. Channeling corporate saving into investment will require elimination of policy distortions and financial sector development including availability of better saving instruments and improved business and investment climates. At the household level, demographic trends, financial development, and precautionary saving are revealed to be important for Asian savers. Two case studies from the PRC and Philippines suggest that these factors are interrelated and complement one another. The surge in urban households' saving in the PRC has two main drivers. First, younger households lack access to credit and accumulate savings in order to purchase durable goods such as televisions, white goods, and automobiles. Second, most urban households undertake precautionary saving as a hedge against risks of illness or other healthcare expenses and in order to finance educational expenses. Hence policies that develop financial markets enabling borrowing against future income, and that rationalize public spending to increase social transfers, reform pension systems, and provide universal health care insurance and education, appear top priorities. These policies would moderate household saving rates and help in rebalancing growth toward consumption.
hdl:11540/4187
Keywords: 330; Sparen; Wirtschaftswachstum; Wohlfahrtsanalyse; Finanzsektor; Philippinen; Asien